Educational Institution in Imperial Brazil: History of Education at the Seminario de Mariana, ecclesiastical formation and Church-State conflict (1844-1875) - Rodrigues Pereira, João Paulo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Objective: This research aims to present elements of the school culture of the Seminary Nossa Senhora da Boa Morte, in the period from 1844 to 1875, corresponding to the episcopate of Dom Antônio Ferreira Viçoso, with the purpose of understanding how the teaching offered by this religious institution was articulated in the context of education in Imperial Brazil. Originality/Contribution: we analyze the school culture of the Mariana Seminary, considered one of the first educational institutions in the province of Minas Gerais, Brazil, which played an important role in cultural formation in the 18th and 19th centuries. Method: It is a qualitative research that, through a bibliographic review and analysis of primary sources, seeks to delve into an educational institution. The premise is that the school is a producer of its own culture capable of promoting cultural transformations. Strategies/Data collection: Some regulations, normative documents, laws and government decrees that intervened in the internal organization of that institution were used as primary sources. In addition to some letters of Dom Viçoso that present relevant information on the educational issue involving the Seminario de Mariana. Conclusions: 1) The bibliographical analysis and the study of primary sources allow understanding specific elements of the Seminary of Mariana as an educational institution with strong characteristics of the religious, political and educational context of Imperial Brazil. 2) The transformations in the school environment of this institution point to the notion of education as something that goes beyond the purely content area, since the valuation of morals appears as a premise for religious human formation.